Infected Abdominal Aortic Aneurysm with Helicobacter cinaedi. (17th January 2016) - Nishida, Kazuhiro; Iwasawa, Takamasa; Tamura, Atsushi; Lefor, Alan T.
Abstract : Helicobacter cinaedi is a rare human pathogen which has various clinical manifestations such as cellulitis, bacteremia, arthritis, meningitis, and infectious endocarditis. We report an abdominal aortic aneurysm infected with Helicobacter cinaedi, treated successfully with surgical repair and long-term antimicrobial therapy.